Optimalisasi Bimbingan “BERKAT” untuk Mendorong Minat Belajar Siswa di Kecamatan Tenjo - Tanti Listiani; Melda Saragih; Kurnia Dirgantoro; Ernie Nababan; Pitaya Rahmadi; Median Adu (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
The "BERKAT" guidance program is a comprehensive approach that focuses on increasing students' interest in learning through structured and sustainable methods. This study used a quantitative method with a quasi-experimental design, with 26 students from various schools in the Tenjo sub-district serving as research samples. Data was collected using a questionnaire to measure the level of interest in learning before and after the mentoring intervention. A t-test was used in data analysis to identify significant differences in learning interests. The results show that "BERKAT" mentorship has a positive and significant influence on increasing students' interest in learning. The average student's increased interest in learning demonstrates this. This research has practical implications for developing community guidance programs to improve the quality of education.